Cigarette smoke impairs NK cell-dependent tumor immune surveillance - Lu, Ling-Min; Zavitz, Caleb C J; Chen, Biao; Kianpour, Sussan; Wan, Yonghong; Stämpfli, Martin R (Journal of Immunology, 2007)
In this study, we investigated the impact of cigarette smoke on tumor immune surveillance and its consequences to lung tumor burden in a murine lung metastasis model. Cigarette smoke exposure significantly increased the numbers of lung metastases following B16-MO5 melanoma challenge. This effect was reversible; we observed significantly fewer tumor nodules following smoking cessation. Using RAG2(-/-) and RAG2(-/-)gamma(c)(-/-) mice, we provide strong evidence that increased tumor incidence was NK cell dependent. Furthermore, we show that cigarette smoke suppressed NK activation and attenuated NK CTL activity, without apparent effect on activating or inhibitory receptor expression. Finally, activation of NK cells through bone marrow-derived dendritic cells conferred protection against lung metastases in smoke-exposed mice; however, protection was not as efficacious as in sham-exposed mice. To our knowledge, this is the first experimental evidence showing that cigarette smoke impairs NK cell-dependent tumor immune surveillance and that altered immunity is associated with increased tumor burden. Our findings suggest that altered innate immunity may contribute to the increased risk of cancer in smokers.